Short- and long-term association between individual levels of milk antibody against Ostertagia ostertagi and first-lactation heifer’s production performances - Bellet, C.; Green, M.J.; Bradley, A.J.; Kaler, J. (Elsevier, 2018)
It is agreed that exposure of adult dairy cattle to helminths on pasture can negatively affect production performances as milking herd. Young animals, especially replacement heifers, represent the future of a dairy farm and are among the most vulnerable to helminth infections in a dairy herd. For this reason, dairy farmers tend to frequently treat heifers against helminths, although the impact of helminths on heifers’ production performances is still poorly understood. Using different epidemiological and serological tools, this study examines the relationship between heifer exposure to helminths on pasture and production performances over time. During a one-year period, 1,454 individual milk samples were collected from first-lactation heifers in England and tested for Ostertagia ostertagi (O. ostertagi) antibodies. After controlling for other confounders, increasing milk antibody levels against O. ostertagi were significantly associated with decreased milk yield at sampling but not at day 305 of heifer lactation. We did not observe any relationship between milk antibody levels against O. ostertagi in heifers and yields in fat and protein. However, heifers with a high level of milk antibodies against O. ostertagi were more likely to produce dead calf at first calving and present a delay in second calving. Moreover, these heifers had significantly higher levels of milk antibodies against Mycobacterium paratuberculosis (M. paratuberculosis) during their first lactation and were more likely to die before the end of the study. We argue that epidemiological approaches can be useful but must be complemented by other methodologies to better understand the impact of helminth infections in dairy heifers. In order to address the complex dynamics of helminth infections in dairy cattle production we require more comprehensive approaches that include triangulation between data sources and interdisciplinary studies.